Women and the Nation-State: An Analysis - Mohd Wani, Gull (International Journal of Psychosocial Rehabilitation, 2020)
Gender Equality and Sustainable Development has been the subject-matter of discussion in many of our academic conferences. We recognize that most positive step towards sustainable future would be to uphold and incorporate Sustainable Development Goals (SDG, s) in all schemes, initiatives and policies to be taken for women and development. These goals contain the potential to empower women and lay the foundation for a just and inclusive social order. A recent study by the world Bank cited by many authors found that countries lose S160 trillion in wealth due to the differences in lifetime earnings between men and women (1) It is significant to revisit the year, 1908 when 15000 women garment workers marched through the New York city protesting sexual harassment, low wages and long hours of work. This in one sense marked the rise of "phenomenal women". In India notably the history of struggle for rights and dignity of women is very much a part of freedom movement whose legacy got transmitted into the nation-building process after 1947.This legacy equally influenced the constitution-making and constitutionalism in post-independence period.